2007
DOI: 10.4049/jimmunol.178.5.3084
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Two Quantitative Trait Loci Controlling Collagen-Induced Arthritis Reveals a New Set of Interacting Subloci

Abstract: Linkage analysis of F2 crosses has led to identification of large numbers of quantitative trait loci (QTL) for complex diseases, but identification of the underlying genes has been more difficult. Reasons for this could be complications that arise from separation of interacting or neighboring loci. We made a partial advanced intercross (PAI) to characterize and fine-map linkage to collagen-induced arthritis in two chromosomal regions derived from the DBA/1 strain and crossed into the B10.Q strain: Cia7 on chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…This mapping resolution is high compared to previous results in arthritis using AIL, or partial AIL,45 46 47 48 49 and it approaches the mapping results for Ncf1 and APLEC in congenic strains (<0.6Mb).…”
Section: Discussionsupporting
confidence: 60%
“…This mapping resolution is high compared to previous results in arthritis using AIL, or partial AIL,45 46 47 48 49 and it approaches the mapping results for Ncf1 and APLEC in congenic strains (<0.6Mb).…”
Section: Discussionsupporting
confidence: 60%
“…We did not obtain as many QTLs for spontaneous arthritis compared to studies using models of CIA (Otto et al ., 1999; Yu et al ., 2006; Ahlqvist et al ., 2007). One possible explanation is that CIA may be regulated by more QTLs than spontaneous arthritis under IL-1ra deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…identified a total of 12 separate QTLs associated with proteoglycan-induced arthritis (Otto et al ., 1999) and MHC-independent QTLs (Otto et al ., 2000). Many QTLs have been finely mapped (Backdahl et al ., 2003; Yu et al ., 2006; Ahlqvist et al ., 2007), and their potential molecular mechanisms and interactions have been studied (Bahabri et al ., 1998; Adarichev et al ., 2003; Glant et al ., 2004; Johannesson et al ., 2005; Martin et al ., 2005; Jensen et al ., 2006; Laragione et al ., 2007). For example, Yu et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Large rodent offspring generated in experimental intercrosses facilitated the identification of epistatic loci outside the MHC (Cia7 with Cia26) 80 and between MHC and non-MHC CIA and AIA loci. [40][41][42] Furthermore, studies in advanced intercross lines, 72,81 bi-congenic 82 and subcongenic strains 31 identified interacting loci in different chromosomes or within the same chromosome. Therefore, epistatic interactions and their functional characterization can be more easily and convincingly characterized in rodents and subsequently tested in RA in a gene-gene specific manner.…”
Section: Advanced Intercross Lines To Refine Arthritis Qtl Intervalsmentioning
confidence: 99%